The “Namaste Sign”—A Novel Coronal MRI Marker for the Evaluation of Anterior Cruciate Ligament Integrity - Shashank Chapala; Rajesh Botchu; Hasaam Uldin; Meili Jade Temsin Leung Chew; Kapil Shirodkar; Sang Bum Lee; Anoop Venkatapura Bylaswamy; Avneesh Chhabra (Journal of Clinical Medicine, 2026)
Magnetic resonance imaging (MRI) is universally recognized as the gold standard for evaluating anterior cruciate ligament (ACL) injuries. However, differentiating partial tears from complete ruptures using the standard sagittal plane remains a diagnostic challenge. The oblique coronal orientation of the ACL often leads to volume averaging artifacts and inaccurate interpretations. While axial imaging offers a favorable alternative, distal tears near the tibial attachment are frequently missed. This review synthesizes current concepts in the anatomical and radiological evaluation of the ACL and introduces the “Namaste sign,” a novel and proposed preliminary imaging marker observed on coronal MRI to help assess ACL integrity. Grounded in the distinct native double-bundle architecture of the ACL, the Namaste sign utilizes the coronal plane to evaluate the transverse relationship and physiological tension of the anteromedial and posterolateral bundles. In a normal knee, these bundles converge symmetrically from their distinct tibial footprints and maintain tight contact with the lateral femoral condyle, mimicking hands pressed together in a traditional “Namaste” gesture. This article details the anatomical basis of this sign, provides a systematic method for its identification, and illustrates how morphological variations such as “broken hands,” “absent hands,” “absent proximal hug,” or “separation of hands” may correspond to specific ACL lesions. As a preliminary conceptual marker, the Namaste sign is intended to serve as an educational adjunct to combined three-plane evaluation rather than a standalone diagnostic criterion. Notably, this sign is not applicable to postoperative ACL reconstructions. A preliminary pilot study of 50 cases utilizing thin-slice MRI (≤3 mm) demonstrated nearly 100% visibility of the sign, 98% diagnostic accuracy, and almost perfect inter-observer agreement between two radiologists with more than 10 years of experience (Cohen’s kappa = 0.92). However, future diagnostic studies with rigorous arthroscopic reference standards are required to establish its clinical performance and reliability in larger cohorts.